Analisis Persistensi Penggunaan Obat Antidiabetik Terhadap Pencapaian Gula Darah Optimal Pada Pasien di Puskesmas - Shinta Bella; Nurmainah Nurmainah; Mohammad Andrie (State University of Gorontalo, 2022)
DM sufferers in Indonesia lack awareness of using drugs regularly and continuously or in clinical terms known as persistence. The persistence of using antidiabetic drugs for 1 year is known to be low (65%). This study aims to analyze the relationship between patient characteristics, patient therapy factors and drug factors used by patients that can affect the persistence of antidiabetic drug use in outpatient type 2 diabetes mellitus patients at Sungai Raya Dalam Public Health Center, Kubu Raya Regency. This study uses a retrospective cohort study design and uses secondary data sources for outpatient type 2 diabetes mellitus patients at Sungai Raya Dalam Public Health Center, Kubu Raya Regency. The persistence measurement method used is the gaps between refill method with a grace period of 14 days for taking the drug. Data were analyzed using chi square test. The number of subjects used were 206 patients with type 2 diabetes mellitus who used antidiabetic drugs (June 2020-June 2021). The results showed that the majority of the characteristics of patients with type 2 diabetes mellitus who visited the Sungai Raya Dalam Public Health Center tended to be 40-60 years old (68.4%), female (54.9%), patients with monotherapy therapy regimen (76.7%). %), patients with metformin (72.3%) and patients with uncontrolled blood sugar (67.5%). Only (43.2%) of patients persistently used antidiabetic drugs. Chi square analysis showed that there was a significant difference between the age factor (p = 0.036), there was no significant difference between gender (p = 0.425), treatment regimen (p = 0.452) and type of therapy (P = 0.121). The conclusion of this study is that the persistence of drug use is influenced by the therapeutic regimen and the type of antidiabetic drug given.